The Role of Inter Professional Rivalry in Trade Disputes Among Medical Personnels in Teaching Hospitals in The Southeast - Udeobasi, Obianuju Chinyelu; Nnonyelu, Austin Nkemdilim (Social Science Research, 2024)
The Nigeria healthcare professionals are the pillars of the health system and a lack of teamwork amongst them is the bane of trade disputes in the sector. The challenges of inter professional rivalry in the health sector particularly in the teaching hospitals is affecting the quality of healthcare delivery in the country. This study examined the role of inter professional rivalry in teaching hospitals in the southeast and incorporate the understanding into meaningful health policies. A sectional design and convergent parallel mixed method research strategy used administer questionnaires and interviews to healthcare personnel. Data were analyzed using Statistical Package for Social Sciences while qualitative data was analyzed using thematic content analysis. A total of 625 respondents were randomly drawn from the teaching hospitals. Findings revealed that majority of the respondents indicated that inter-professional rivalry and trade disputes are prevalent in health sector. findings also indicate that fractionalization of unions whereby each profession wants to be recognized and given precedence by government has ridden the health sector with disputes. It is on this score that this study recommends that government should conduct regular wage reviews so as to bridge the gap in wage differentials among Nigerian health workers and decrease the lingering industrial disharmony and frequent strikes by respective unions. Also all health workers should work together in harmony and respect each other, learn to relate or coexist with one another peacefully without interference.